Ruflorinia papillosa sp. nov. from the Lower Cretaceous of Patagonia, Argentina - Villar, Liliana Monica (2000)
The morphology and cuticle of the caytonialean leaf Ruflorinia papillosa sp. nov. from the Estancia Bajo Tigre of the Baqueró Formation (Lower Cretaceous), Patagonia, Argentina, were studied, using light microscopy (LM), and scanning and transmission electron microscopy (SEM and TEM). The morphological, anatomical and ultrastructural analyses of the leaves have shown the presence of strong xeromorphic characters that suggest the plants were living under stressful conditions and probably grew on dry soils exposed to intense solar radiation.